THE CYCLOID MAGNETIC GEAR BASED ON HALBACH ARRAY - HAO WeiNa; ZHOU Jun (Jixie qiangdu)
The cycloid magnetic gear transfers speed through the inner rotor rotation and revolution to get a higher transmission ratio and torque density. The permanent magnets were arranged by Halbach in order to improve the magnetic flux leakage and the utilization of permanent magnets,and a prototype was designed and manufactured according to the working principle. The magnetic field distribution and static torque characteristics of the cycloid permanent magnetic gear were researched by finite element simulation. Comparing with the general structure,it shows that the maximum torque density of even value can be increased by about 30% using 90° Halbach structure which has smaller fluctuations. Finally,the transmission torque of different angle were tested by experiments,the results are in accord with simulated results.